EFFECTIVENESS OF LITERATURE CIRCLES ON STUDENTS’ READING COMPREHENSION - Dini Irawati (Center of Language and Cultural Studies [CLCS], 2016)
This study reports an experimental study to see the effect of literatures circles to improve reading comprehension of English department students of State Islamic Institute (IAIN) of Samarinda. A quasi experimental research using nonrandomized control group pretest-posttest design was conducted to see effectiveness of literature circles on students’ reading comprehension. A number of 24 students were taken as sample from the first semester students joining in an intensive English course program in academic year 2011/2012. Using independent t-test, the analysis of the posttest means the finding yielded a t-value of 3.11. The t-value (3.11) is higher than the critical table 1.678 at p=.05 and df=44 (one-tailed). The result evidently shows that literature circles contribute a significant effect to improve students’ reading comprehension.